Economic Growth and the Expanding Public Sector: A Reexamination - Conte, Michael A.; Darrat, Ali F. (The Review of Economics and Statistics, 1988)
Utilizing a Granger causality approach, the authors test whether there has been a causal rela tion between public sector growth and real economic growth rates for the OECD countries. Special emphasis is laid on feedback effects from economic growth to government growth that result from macroeconomic policy. The authors find that government growth has had mixed effects on economic growth rates, positive for some countries and negative f or others. However, for the majority of the OECD countries, there was no discernable impact of government growth on the rate of real econo mic growth. Copyright 1988 by MIT Press.